2020
DOI: 10.1021/acsami.0c14983
|View full text |Cite
|
Sign up to set email alerts
|

Surgery-Guided Removal of Ovarian Cancer Using Up-Converting Nanoparticles

Abstract: Ovarian cancer survival and recurrence rate are drastically affected by the amount of tumor that can be surgically removed prior to chemotherapy. Surgeons are currently limited to visual inspection, making smaller tumors difficult to remove surgically. Enhancing the surgeon's ability to selectively remove cancerous tissue would have a positive effect on a patient's prognosis. One approach to aid in surgical tumor removal involves using targeted fluorescent probes to selectively label cancerous tissue. To date,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Based on these findings, in the last two decades, CA125 has found application as a tumor marker or biomarker in many cancer types, most notably in ovarian cancer 149 . Numerous studies have demonstrated elevated levels of CA125 in ovarian cancer tissues when compared to healthy, 150,151 and to date, the transmembrane cell‐surface protein CA125 remains the most‐used molecular ovarian cancer marker 152 . Moreover, despite CA125 mainly representing a serum biomarker, since high concentrations of MUC16 /CA125 remain on the surface of ovarian cancer cells, it could represent a reliable biomarker for targeted detection of ovarian cancer through imaging techniques 153 …”
Section: Membrane‐associated Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, in the last two decades, CA125 has found application as a tumor marker or biomarker in many cancer types, most notably in ovarian cancer 149 . Numerous studies have demonstrated elevated levels of CA125 in ovarian cancer tissues when compared to healthy, 150,151 and to date, the transmembrane cell‐surface protein CA125 remains the most‐used molecular ovarian cancer marker 152 . Moreover, despite CA125 mainly representing a serum biomarker, since high concentrations of MUC16 /CA125 remain on the surface of ovarian cancer cells, it could represent a reliable biomarker for targeted detection of ovarian cancer through imaging techniques 153 …”
Section: Membrane‐associated Targetsmentioning
confidence: 99%
“…Marotta et al have developed silica‐coated UCNPs (Yb‐Ho‐SiO 2 ‐2) for in vivo ovarian cancer detection, combining the high TAMs‐targeting ability of SiNPs and the advantageous spectroscopic properties of the upconverting inorganic nanoparticles 150 . Excited by multiple photons, with a longer wavelength (NIR), UCNPs can emit a single, high‐energy photon, with a shorter wavelength (UV‐Vis) 20 .…”
Section: Extracellular Targetsmentioning
confidence: 99%
“…Visual resection was found to leave ≈10.7% of tumor mass following surgical removal whereas the UCNP‐aided design reduced the residual tumor mass to 0.2%. [ 221 ]…”
Section: Applications Of Ucnps In Multimodal Bioimagingmentioning
confidence: 99%
“…Visual resection was found to leave %10.7% of tumor mass following surgical removal whereas the UCNP-aided design reduced the residual tumor mass to 0.2%. [221] UCNPs could further open new opportunities in clinical imaging that are currently unachievable with X-ray, magnetic resonance imaging (MRI), positron emission tomography (PET), and ultrasound techniques. Two examples were shown by utilizing UCNPs to improve surgical accuracy: the potential for molecular and protein targeting; and instant, visual feedback of optical signal.…”
Section: Applications Of Ucnps In Multimodal Bioimagingmentioning
confidence: 99%
“…Fluorescent silica nanoparticles (SiNPs) with a diameter range of 200–1000 nm selectively accumulate in the TAMs of abdominal metastatic ovarian cancer in a murine model [ 115 ]. Marotta et al [ 94 ] combined upconverting nanoparticles (UCNPs) with SiNPs, generating a visible light signal by NIR excitation to enhance the tumor boundary profile in real-time surgical resection and provided a simple and feasible imaging scheme for operation guidance. Image analysis showed that compared with vision-based surgical resection, the number of residual tumors after image-guided surgery was significantly reduced.…”
Section: Principlesof Designing Tams Imaging Nanoprobesmentioning
confidence: 99%